An Analysis of Impoliteness Strategies in Turning Red Based on Culpeper's Theory of Pragmatics - Nurjanah, Siti Fatimah; Maisa; Haris Budiana; Faisal Zachrie; Ariq Nurfauzan (University of Chitral Journal of Linguistics and Literature, 2024)
The pragmatic analysis has become progressively noteworthy in understanding impoliteness strategy in recent years, especially in the movie pragmatics analysis. This study examines the types of impoliteness strategies used in the movie Turning Red. The method of qualitative design is qualified to deal with it. The data was collected by watching the movie repeatedly and taking notes during the conversation. The data were analyzed using impoliteness strategies in the Culpeper framework. The result showed that thirteen utterances consisted of three utterances of baldness on record, four utterances of positive impoliteness, five utterances of negative impoliteness, and one utterance identified as sarcasm or mock politeness. However, there is one strategy that is not found in the movie: withholding politeness. It means that this movie is intended to show the negative facial desires and put the environment in negative situations, interfering with their freedom of action and humiliation.